Postwar industrial policy in Japan : - Boger, Karl (The Scarecrow press, 1988)
The Japanese 'economic miracle' caught the U.S. by surprise, and relatively few studies in English were published about the postwar economic policies of Japan before 1970. Myths about a monolithic government-industry collaboration in Japan stereotyped the Japanese economy under the rubric of 'Japan, Inc.,' and there was a paucity of factual information. Japan's international competitive success has forced an end to this research gap. This bibliography, organized by chapters on industrial policy, economic development, technology, finance, productivity, and other topics, provides a guide to works on Japanese industrial policy and its role in the postwar performance of the Japanese economy